Exposure to endocrine disruptors and alterations in mineralized tissues: A Narrative Review. - Paula Contreras-Meza; Jaime A. Jacques (Journal of Oral Research, 2022)
Background: Endocrine Disrupting Chemicals (EDCs) would cause alterations in organs/systems of exposed individuals or their progeny. Objetive: To identify and analyze the main published findings on the effects of exposure to EDCs on teeth, cartilage, and bone. Material and Methods: Two databases were analyzed: Medline and Web of Science. Only observational studies analyzing the effect of EDCs on mineralized tissues published since 2006 were included in the study. Results: 25 articles were selected, most of them involving EDCs pesticides, plasticizers, or personal care products, highlighting organochlorine compounds, bisphenols, phthalates, dioxins, parabens, and perfluoroalkyls. Thirty-six per cent of the studies reported an accumulation of EDCs in teeth or bones, while 64% reported alterations in their development or morphology, mainly at the bone level, primarily affecting their mineral density and size, as well as that of the bones of exposed individuals or their progeny. The type of effect observed was related to the EDCs analyzed, and it seemed to depend on variables such as age, sex, ethnicity/race, and even the metabolic status of the individuals in the different species analyzed. No evidence associated with effects on cartilage was found. Conclusion: EDCs in the environment, at work, or at home, under different exposure routes, are capable of accumulating in teeth and bone, particularly affecting the latter. It is necessary to study the effect of EDCs on mineralized tissues in agro-industrial areas, especially on teeth.